ijsr 2020
DOI: 10.36106/ijsr/1019867
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Perception of Post-Graduates and Interns of a Medical Institution Towards Nicotine Replacement Therapy: A Cross-Sectional Survey in Bangalore City, Karnataka

Abstract: TITLE: - Knowledge, Attitude and Perception of Post-graduates and Interns of a medical institution towards Nicotine Replacement Therapy: A cross-sectional survey in Bangalore city, Karnataka. AIMS & OBJECTIVE: The main objective of this survey was to assess knowledge, attitude and practices of post-graduates and interns of a medical institution towards nicotine replacement therapy and provide baseline data for future research towards nicotine replacement therapy. METHODOLOGY: A descriptive cross‑sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Bad experiences from previous illnesses have also been identified as a determinant of the severity assessment [ 8 ]. Several authors have documented the underestimation of signs of severe illness in neonates attributable to maternal educational level [ 8 , 13 , 17 , 22 , 23 ]. The findings in this study contradict those of several studies conducted in rural communities of Africa and Asia where fever and jaundice were seen as danger signs requiring immediate medical intervention [ 8 , 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bad experiences from previous illnesses have also been identified as a determinant of the severity assessment [ 8 ]. Several authors have documented the underestimation of signs of severe illness in neonates attributable to maternal educational level [ 8 , 13 , 17 , 22 , 23 ]. The findings in this study contradict those of several studies conducted in rural communities of Africa and Asia where fever and jaundice were seen as danger signs requiring immediate medical intervention [ 8 , 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It found that, because they are aware of reduce, recycle, and reuse, the majority of households, about 71%, are willing to utilize recyclable materials to transport vegetables, grains, and other items from entire shops/markets (R3). A higher level of community participation in trash reduction at the source through scientific campaigns was required (Kumar & Nandini, 2013). Another study in Malasiya checked the education level and peoples perception.…”
Section: Management Practice Of Solid Wastesmentioning
confidence: 99%